Racialisation and racial formation in urban spaces*. (2nd January 2019) - Alfredo Guimarães, Antonio Sérgio
ABSTRACT: In this paper, I try to clarify the notions of racialisation and racial formation and how they operate in the framework of nation states like Brazil. My main argument is that these processes are always constrained by the formation of social classes and national cultural repertoires even if transnational forces are important in nurturing them. I conclude by making a preliminary effort to unravel mechanisms and institutions which allow these processes of racialisation and racial formation to form part of the daily lives of black Brazilians in the context of class-structured urban spaces.